Theoretical investigations on modeling blood flow through vessel for understanding effectiveness of magnetic nanocarrier drug delivery systems - Alzhrani, Rami M.; Aldawsari, Mohammed F.; Alamoudi, Jawaher Abdullah (Frontiers in Medicine, 2024)
For cancer therapy, the focus is now on targeting the chemotherapy drugs to cancer cells without damaging other normal cells. The new materials based on bio-compatible magnetic carriers would be useful for targeted cancer therapy, however understanding their effectiveness should be done. This paper presents a comprehensive analysis of a dataset containing variables x(m), y(m), and U(m/s), where U represents velocity of blood through vessel containing ferrofluid. The effect of external magnetic field on the fluid flow is investigated using a hybrid modeling. The primary aim of this research endeavor was to construct precise and dependable predictive models for velocity, utilizing the provided input variables. Several base models, including K-Nearest Neighbors (KNN), Decision Tree (DT), and Multilayer Perceptron (MLP), were trained and evaluated.Additionally, an ensemble model called AdaBoost was implemented to further enhance the predictive performance. The hyper-parameter optimization technique, specifically the BAT optimization algorithm, was employed to fine-tune the models. The results obtained from the experiments demonstrated the effectiveness of the proposed approach. The combination of the AdaBoost algorithm and the Decision Tree model yielded a highly impressive score of 0.99783 in terms of R 2 , indicating a strong predictive performance. Additionally, the model exhibited a low error rate, as evidenced by the root mean square error (RMSE) of 5.2893E-03. Similarly, the AdaBoost-KNN model exhibited a high score of 0.98524 using R 2 metric, with an RMSE of 1.3291E-02. Furthermore, the AdaBoost-MLP model obtained a satisfactory R 2 score of 0.99603, accompanied by an RMSE of 7.1369E-03.